2020
DOI: 10.1002/mgg3.1473
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic diversity, forensic feature, and phylogenetic analysis of Guizhou Tujia population via 19 X‐STRs

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…The same and similar ethnolinguistic and geographical cluster characteristics observed in our study were also be reported using other genetic markers, such as autosomal STRs and X chromosomal STRs (X-STRs). Take, for example, 15 autosomal STR loci [ 19 ] and 19 X-STRs [ 13 ] based on the same statistical methods in our previous phylogenetic relationship analysis; Guizhou Tujia had an intimate relationship with geographically close populations and the Han populations, whereas far distant from the Tibeto-Burman language-speaking populations. Totally, our findings based on the 37 Y-STRs demonstrate that Guizhou Miao and Guizhou Tujia are genetically similar with geographically close populations and other linguistically close populations, which is in accordance with the autosomal STR and X-STR consequences of geography and language classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same and similar ethnolinguistic and geographical cluster characteristics observed in our study were also be reported using other genetic markers, such as autosomal STRs and X chromosomal STRs (X-STRs). Take, for example, 15 autosomal STR loci [ 19 ] and 19 X-STRs [ 13 ] based on the same statistical methods in our previous phylogenetic relationship analysis; Guizhou Tujia had an intimate relationship with geographically close populations and the Han populations, whereas far distant from the Tibeto-Burman language-speaking populations. Totally, our findings based on the 37 Y-STRs demonstrate that Guizhou Miao and Guizhou Tujia are genetically similar with geographically close populations and other linguistically close populations, which is in accordance with the autosomal STR and X-STR consequences of geography and language classification.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used multifarious bioinformatics methods (Rst genetic distance, heatmap, UPGMA, MDS and PCA) to reconstruct the population relationship of Guizhou Tujia and diverse ethnic groups from nine major language families coming from 11 countries (Sinitic: Han, Hui; Tai-Kadai: Bouyei, Dong, Laotian, Thai; Tibeto-Burman: Tibetan, Tujia; Hmong-Mien: Miao, Yao; Turkic: Uighur, Kazakh; Mogolian: Mogolian, Daur; Indo-European: Danish, Indian, Italian; Semito-Hamitic: Bahraini, Arab; Independent: Korean, Japanese). These bioinformatics methods generally employed the population comparisons in the forensic medicine [13][14][15][16][17]. The results showed that there were significant genetic differences between populations belonging to different regions and languages.…”
Section: Discussionmentioning
confidence: 99%
“…Uyghur derived western related ancestry from West Eurasians and South Asians, while the eastern related components were from the East Asians, and the Siberians ( Ma et al, 2014 ; Feng et al, 2017 ; Heizhati et al, 2020 ). Gansu province connecting the Hexi Corridor and the Tibetan-Yi Corridor in northwest China is not only takes part in the west-east Eurasian communication, but also plays an important role in the southwards population expansion which contributed to the formation of Tibeto-Burman speaking population ( Feng et al, 2020 ; Luo et al, 2020 ). Human population genetic researches had been carried out based on low-density genetic markers and limited sample sizes to explore the genetic history of Gansu province ( Yao et al, 2016 ; Yao et al, 2017 ; Wen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%